The bioenergetics of sports performance - Morton, J. P.; Close, G. L. (Strength and conditioning for sports performance, 2016)
The fundamental goal of the strength and conditioning (S&C) specialist should be to alter the characteristics of the muscle fibre so that it can perform better during the metabolic demands that arise during the specific sporting activity. For example, with the appropriate training stimulus, the muscle fibre may change in size, structure and composition so that it produces more force (e.g. muscle hypertrophy). Alternatively, the fibre may become more fatigue resistant if it develops endurance-like properties, as is typical of that occurring with endurance training. In such circumstances, the fibre now expresses more mitochondria per gram of muscle tissue (i.e. mitochondrial biogenesis), which is typically recognised functionally by improvements in the lactate threshold. In order to induce the appropriate phenotype conversion, it is crucial for the S&C coach to understand the bioenergetics of muscular activity. Indeed, sport-specific training programmes, and subsequent performance enhancement, can only be developed if (and when) a sound understanding of energy metabolism is acquired. Energy-yielding processes have typically been described as aerobic (i.e. energy is produced with the utilisation of oxygen) or anaerobic (i.e. energy is produced without the use of oxygen). In its simplest terms, the 100 m sprinter relies predominantly on anaerobic metabolism, whereas the marathon runner relies on aerobic metabolism. However, there are many sporting events that exist on the continuum between these two extremes and that require appropriate development of both the anaerobic- and the aerobic-producing pathways in order to maximise performance during competition (see Figure 4.1). The aim of this chapter is to outline the bioenergetics of human performance so that the S&C coach will possess an adequate understanding of energy metabolism in order to design sport-specific training programmes. The reader is first introduced to an overview of energy systems and storage, followed by a more detailed discussion of the biochemical pathways by which carbohydrates (CHO) and lipids are used to provide energy. We then proceed to specifically discuss how energy-producing pathways interact to fuel muscular activity during strength (and power), endurance and high-intensity intermittent sports.